DIGITAL MARKETING AND EXPERIENTIAL MARKETING IN BUILDING CUSTOMER LOYALTY THROUGH TRUST - Raodatul Jannah; Eko Budi Satoto; Nurul Qomariah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the role of digital marketing and experiential marketing in shaping customer loyalty through customer trust in micro-culinary businesses, particularly angkringan in Situbondo Regency. The rapid growth of digital platforms has changed how small food vendors interact with consumers, yet many traditional businesses still face challenges in converting digital engagement and on-site experiences into sustained loyalty. This research addresses how digital marketing and experiential marketing influence customer loyalty and whether customer trust mediates these relationships. The study offers novelty by integrating both marketing approaches into a single structural model, positioning customer trust as an intervening variable within the underexplored context of traditional micro-culinary businesses. A quantitative method was applied using a cross-sectional survey of 385 angkringan customers. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results show that digital marketing and experiential marketing have positive and significant effects on both customer trust and customer loyalty. Customer trust also significantly influences loyalty and partially mediates the relationship between experiential marketing and loyalty. The findings highlight the importance of combining digital strategies with meaningful customer experiences to build trust and sustain long-term customer loyalty.